Evaluation of capital investments in advanced manufacturing technologies - Sim, Mong Whatt. (2009)
Advanced manufacturing Technologies (AMT) have been identified as the technologies for manufacturing firms to gain a competitive edge over its competitors and also to ensure long term survival. However, its incorporation in such firms has been difficult as a result of its heavy investment cost which traditional justification criterion such as payback period, etc have not been very convincing.